Metals recovery from spent Zn-MnO2 batteries by Hydrometallurgy - Nogueira, Carlos (2010)
A hydrometallurgical process for recycling spent Zn-MnO2 batteries was developed, involving leaching with sulfuric acid, purification by precipitation and metals separation for further recovery. Leaching of zinc oxide was easily attained while for manganese oxide was rather difficult depending on temperature and acid concentration. At 90ºC and with the liquid/solid ratio of 20 L/kg, more than 95% of zinc is recovered in 30 minutes with 0.5M H2SO4. To attain similar recovery for manganese, higher levels of acid concentration and time are needed (e.g 0.7 M and 2 hours). After leaching a purification step is necessary to remove iron co-dissolved through Fe(III) precipitation. Separation of zinc from manganese by solvent extraction with 1M DEHPA follows in the process route. The countercurrent multistage separation diagram developed allows the production of a zinc electrolyte with 120 g/L Zn and 0.005 g/L Mn, and a raffinate with 16 g/L Mn and 0.013 g/L Zn.